PENEGAKAN HUKUM TERHADAP EKSPLOITASI ABK WNI PADA KAPAL IKAN TIONGKOK LU HUANG YUAN YU DI PERAIRAN KEPULAUAN RIAU - Sinta, Dewi; Arman, Zuhdi (LPPM Universitas Putera Batam, 2021)
ABSTRACT It is suspected that there has been a criminal act of trafficking in persons which resulted in the exploitation of Indonesian crew members on the Lu Huang Yuan Yu fishing boat. This study aims to see how the factors of law enforcement including the obstacles and solutions experienced by law enforcement officers in this case. This research is a type of empirical legal research that uses primary data from interviews at the Riau Islands Regional Police as the main source by using qualitative descriptive methods as data analysis methods. The results of this study indicate that the Riau Islands Police, Batam District Attorney, and Batam District Court have enforced the law on this case as a form of repressive legal protection even though there are obstacles, namely there has been a judge's decision that has permanent legal force for the criminal act of persecution that made Song Chuanyun suspect. Als Song can no longer be prosecuted for the crime of trafficking in persons with the same location and time of occurrence. The solution used by the Riau Islands Police was to use the phrase “and/or” in the Minutes of Investigation which indicated that Song Chuanyun A.k.a Song had participated in the crime of trafficking in persons. These constraints and solutions do not provide legal certainty because they do not provide a deterrent effect for the perpetrators.